Polityczne i prawne aspekty prowadzenia badań naukowych w rejonach polarnych - Świątecki, Aleksander; Górniak, Dorota; Zdanowski, Marek; Grzesiak, Jakub; Mieczan, Tomasz (Studia Prawnoustrojowe, 2019)
The Arctic and Antarctic have been of great interest to the international community for a number of years. The still unresolved problem regarding polar regions is the still partially regulated legal issues concerning the management of these areas. Both the Arctic and Antarctica are areas of potentially great scientific, economic, political and military importance. The political and legal status of polar areas is not uniform. Currently, there is no legal international document that would regulate issues related to the management of the Arctic region. The political and legal status of Antarctica was determined in 1959 in Washington. The Antarctic treaty regulates in detail the activities in this region. Territorial claims are a particularly important problem. A number of countries prove their territorial rights to both the Arctic and Antarctic. The Arctic division is discussed within five countries, without the participation of the international community, while the Antarctic Treaty arrangements have put these issues on ice until 2049. International cooperation in the field of research of polar regions has a long history and is confirmed by bilateral and international agreements. Conducted research in the Arctic and Antarctic relate to various scientific problems. Investigations of processes taking place on Earth on a global scale are of particular importance, both in historical and prognostic perspective. The history of Polish polar research is rich, multi-faceted and dates back to the second half of the nineteenth century. Contemporary Polish polar research focuses on a number of problems: glaciology and periglacial phenomena, climatology, geomorphology, hydrology, and geo-ecosystems dynamics. Polish scientific activity, in these regions, significantly develops our positive relations with the international community.